Plant responses to elevated CO2 levels in soils: distinct CO2 and O2-depletion effects - Lake, Janice A.; Steven, Michael D.; Smith, Karon L.; Lomax, Barry H. (Elsevier, 2016)
To investigate potential environmental effects in the context of carbon dioxide (CO2) leakage from Carbon Capture and Storage (CCS) schemes, the University of Nottingham ASGARD (Artificial Soil Gassing And Response Detection) facility, was used to inject CO2 into the soil in replicated open-air field plots over several seasons to measure the effects on UK crop species. However, this system lacked a way of distinguishing the concomitant effects of oxygen (O2)-depletion (occurring as a consequence of high CO2 levels in the soil). As plants are aerobic, they require O2 for functional integrity of root processes. Here a complementary laboratory system was used to specifically identify distinct CO2 and O2-depletion effects on two crop species, beetroot and wheat. Parameters measured (photosynthetic rate, transpiration rate, stomatal conductance and biomass) between CO2-gassed, nitrogen (N2)-gassed (O2-depletion control) and non-gassed control plants showed distinct differences in response to CO2 gassing and O2-depletion. Differences between field and laboratory studies illustrate effects of variable meteorological conditions in the field, whilst more stable laboratory conditions show differences between crop species. Results show that the interactions of these two stresses (very high soil CO2 and O2 depletion) on crop physiology are discrete and complex.